Vietnam's industrial policy : - Perkins, Dwight H. (United Nations Development Programme in Vietnam (UNDP Vietnam), 2009)
This policy dialogue paper examines areas in which government initiatives can contribute to make this happen by spurring entrepreneurial activity, promoting an enabling business environment and an even playing field and, ultimately, encouraging the development of a strong and globally competitive enterprise sector in Viet Nam. This includes interventions in areas such as investment climate, state-owned enterprise reform, regulation and competition law, financial sector development or infrastructure growth, especially, in this latter case, with regard to the energy and transport sectors.